2023
DOI: 10.1111/1365-2435.14461
|View full text |Cite
|
Sign up to set email alerts
|

Foliar herbivory modifies arbuscular mycorrhizal fungal colonization likely through altering root flavonoids

Zhenlong Xing,
Tiantian Ma,
Libo Wu
et al.

Abstract: Insect herbivory may influence arbuscular mycorrhizal (AM) fungal colonisation by changing plant chemistry, and these effects can vary from negative to positive. Yet the underlying mechanisms are unclear. We investigated AM fungal colonization of Chinese tallow tree (Triadica sebifera) after exposing its seedlings to four different foliar‐feeding insects at two levels of herbivory. We then examined the potential role of induced carbon allocation and secondary metabolites, particularly flavonoids, in AM fungal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 101 publications
1
1
0
Order By: Relevance
“…In this study, in comparison with previous studies of other plant species under AMF treatment, our experiment observed a high level of AMF colonization in the roots of W. trilobata [15,32]. Symbiosis with AMF also resulted in a significant increase in the biomass and stem length of W. trilobata.…”
Section: Effects Of Amf On Invasive Plant Growthsupporting
confidence: 69%
“…In this study, in comparison with previous studies of other plant species under AMF treatment, our experiment observed a high level of AMF colonization in the roots of W. trilobata [15,32]. Symbiosis with AMF also resulted in a significant increase in the biomass and stem length of W. trilobata.…”
Section: Effects Of Amf On Invasive Plant Growthsupporting
confidence: 69%
“…intensity of damage incurred on plants and the duration of herbivory. We speculate that variation in herbivory intensity and duration in previous studies may have led to the observed inconsistent results (Gehring & Bennett, 2009), and symbiosis signals in roots and root exudates may mediate the contrasting responses of AM colonisation (Xing, Ma, et al, 2024). A particularly interesting result was that mechanical damage did not enhance AM colonisation, which could indicate that in addition to wounding, specific compounds present in the oral secretions of the caterpillars are required to elicit the plant responses that result in enhanced AM colonisation.…”
Section: Discussionmentioning
confidence: 87%